ANALISIS PENERAPAN PENYAJIAN LAPORAN KEUANGAN PADA ORGANISASI NIRLABA BERDASARKAN PSAK N0 45 - Daniel Bagus Prakosa Fadjar Harimurti (Universitas Slamet Riyadi, 2014)
The purpose of this research are: 1) To understand the application of accounting at the l Church Pentecosta Church envoy Kartasura. 2) To determine the suitability of the financial statements presented by the Church Pentecostal Church envoy Kartasura with Statement of Financial Accounting Standards No. 45 of the Financial Reporting Nirlaba. Research Organization this form of case studies, in which the research object is selected Envoy Church Pentecostal Church Kartasura. Types of data used is qualitative data and quantitative data. Source of data used are primary data and secondary data. Data were analyzed using descriptive comparative form: 1). Analysis of accounting records include documents used Envoy Church Pentecostal Church Kartasura. 2) compare the financial statements of the Church Pentecostal Church envoy Kartasura with the provisions contained in SFAS No. 45. Output this study indicate that: 1) Recording of the financial transactions in the Church Pentecostal Church envoy Kartasura still has not been systematically and still simple. This was due to the use of documents that have not been in accordance with generally accepted standards, such as not applied journals. 2) The financial statements are presented by the Church Pentecostal Church envoy Kartasura is not in accordance with the financial statements required in SFAS No. 45. That is because the Church Pentecostal Church envoy Kartasura not present the complete financial statements, and some estimates are still using an imprecise term. 3) The results of questionnaires with a total score of 4 and included in the assessment criteria are not appropriate. Keywords: Financial Statements, the Company Nonprofit, Accounting